The Correlation Between Saudi EFL Students Motivational and Attitudinal Behaviors and their Performance and Academic Achievement in English Language - Dhawi M, Al-Mohanna Ayedh (International Journal of Asian Social Science, 2017)
Research demonstrates that language learners’ motivation and attitudes are a standout amongst the most imperative factors that can impact the success or failure in learning that language. Along these lines, the principle point of the present study is to investigate Saudi EFL learners’ motivation for learning English and their attitudes toward learning the language and toward its native speakers. It also looks at the correlation between their motivational and attitudinal behavior and their performance and academic achievement in English language. In addition, it makes some pedagogical implications, based on the findings. A questionnaire and an interview were developed and used to collect data from participants. A total of sixty Saudi students, who were enrolled in intensive English courses at different universities in Canada, participated in the questionnaire, and thirty (half of the specimen) of them were arbitrarily chosen to partake in a subsequent meeting. The aftereffects of the survey and the meeting demonstrated that most of the Saudi EFL understudies had high inspiration to learn English, uplifting states of mind toward learning English and inspirational dispositions toward the local English speakers. They also revealed that there was a clear positive correlation between Saudi EFL students’ motivational and attitudinal behavior and their performance and academic accomplishment in the language.